ADVANCES IN THE DIAGNOSIS AND MANAGEMENT OF INTERNAL DISEASES: A COMPREHENSIVE REVIEW - Xatamov Vohidjon Baxtiyorovich (Western European Studies, 2025)
Internal diseases encompass a broad spectrum of conditions affecting various organ systems, requiring multidisciplinary approaches for effective diagnosis and management. This article explores recent advancements in the study of internal diseases, emphasizing epidemiology, diagnostic innovations, therapeutic strategies, and preventive measures. By integrating global research perspectives, this paper aims to provide a holistic understanding of internal diseases and their implications for public health
Keywords: Internal medicine; chronic diseases; diagnostics